Vietnam war biographies - Hillstrom, Kevin (U-X-L Vietnam War reference library., 2001)
Presents biographical profiles of sixty men and women from the United States and Vietnam who participated in or were affected by the Vietnam War, arranged alphabetically, with sidebars, cross-references, photographs, time lines, and cumulative subject indexes.